#### Answer

$dy=-2\csc(2x)\cot(2x)dx$

#### Work Step by Step

$y=csc2x$
$\frac{dy}{dx}=-csc(2x)cot(2x)\times2$ (derivative of cscx, chain rule)
$dy=-2csc(2x)cot(2x)\times dx$

Published by
Brooks Cole

ISBN 10:
1-28505-709-0

ISBN 13:
978-1-28505-709-5

$dy=-2\csc(2x)\cot(2x)dx$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.